KENDALA GURU DALAM PEMBELAJARAN TEMATIK JARAK JAUH SELAMA MASA PANDEMI COVID-19 DI MADRASAH IBTIDAIYAH NURUL UMMAH (MINU) KOTAGEDE YOGYAKARTA - Khanan Auladi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2020)
This article aims to examine teacher constraints in distance thematic learning in a private school in Yogyakarta. The data in this study were obtained from observations, interviews, and documentation. The results of the study show that distance learning has components, functions, models and challenges in its application. Thematic distance learning in MINU serves as a substitute for conventional learning that has been carried out so far. The model used is Fully Online. In its implementation, the teacher experiences various obstacles both internal constraints of the educator himself and constraints outside the educator. The internal obstacle of educators is the lack of readiness of educators at the beginning of the implementation of distance thematic learning, because most have never attended distance learning training. While the obstacles outside the educator are related to substandard internet connections, mentoring of student guardians that are less than optimal, and students who are getting bored with distance learning. The contribution of this research to education in Indonesia is to illustrate the obstacles that will be faced by teachers in distance thematic learning. Distance learning training is immediately given to teachers so that distance learning can be done optimally.